Estimating the full public health value of vaccination. Issue 46 (1st November 2017) - Gessner, Bradford D.; Kaslow, David; Louis, Jacques; Neuzil, Kathleen; O'Brien, Katherine L.; Picot, Valentina; Pang, Tikki; Parashar, Umesh D.; Saadatian-Elahi, Mitra; Nelson, Christopher B.
Abstract: There is an enhanced focus on considering the full public health value (FPHV) of vaccination when setting priorities, making regulatory decisions and establishing implementation policy for public health activities. Historically, a therapeutic paradigm has been applied to the evaluation of prophylactic vaccines and focuses on an individual benefit-risk assessment in prospective and individually-randomized phase III trials to assess safety and efficacy against etiologically-confirmed clinical outcomes. By contrast, a public health paradigm considers the population impact and encompasses measures of community benefits against a range of outcomes. For example, measurement of the FPHV of vaccination may incorporate health inequity, social and political disruption, disruption of household integrity, school absenteeism and work loss, health care utilization, long-term/on-going disability, the development of antibiotic resistance, and a range of non-etiologically and etiologically defined clinical outcomes. Following an initial conference at the Fondation Mérieux in mid-2015, a second conference (December 2016) was held to further describe the efficacy of using the FPHV of vaccination on a variety of prophylactic vaccines. The wider scope of vaccine benefits, improvement in risk assessment, and the need for partnership and coalition building across interventions has also been discussed during the 2014 and 2016 Global Vaccine and Immunization Research Forums and the 2016 Geneva Health Forum, as well as in numerous publications including a special issue of Health Affairs in February 2016. The December 2016 expert panel concluded that while progress has been made, additional efforts will be necessary to have a more fully formulated assessment of the FPHV of vaccines included into the evidence-base for the value proposition and analysis of unmet medical need to prioritize vaccine development, vaccine licensure, implementation policies and financing decisions. The desired outcomes of these efforts to establish an alternative framework for vaccine evaluation are a more robust vaccine pipeline, improved appreciation of vaccine value and hence of its relative affordability, and greater public access and acceptance of vaccines.